Traumatic effects of lightning strike on human bone morphology and ultrastructure - Bacci, Nicholas (My University, 2016)
South Africa reports lightning fatality rates as high as 8.8 per million annually. Traditionally, forensic lightning fatality identification consists of soft tissue traumatic pattern recognition. This does not allow for manner of death identification in cases of full skeletonization. This study has expanded upon our earlier research, which identified characteristic patterns of lightning disruption in non-human bone. We thus explored the effects of induced lightning high voltage current on human cadaveric material in order to recognise electrically induced trauma. The objectives comprised analysis of microstructural damage through conventional thin-section histology, micro-focus computed tomography and histomorphometry. Experimentation was undertaken on bone blocks extracted from human lower limbs obtained from cadaveric specimens. An experimental system for simulated lightning induction to bone was developed and investigations were carried out on twenty-two bone block specimens. Micro-focus computed tomography was undertaken prior and after experimental treatment; while three blocks were used unmodified as control samples. Thin sections were obtained following post-trauma imaging. Measurements and photomicrographs of the alteration patterns were taken, while micro-focus computed tomography data were reconstructed and visualised as 2D orthoslices and 3D rendered volumes. Results indicated a poor efficiency of micro-focus computed tomography to resolve traumatic features in cortical bone. However, conventional histological methods demonstrated cortical bone trauma patterns well, allowing easy identification. Statistical analyses demonstrated relationships between current intensity and extent as well as typology of damage observed. The relationships identified suggested a dual mechanism of bone trauma, consisting of a combination of both electrically and thermally induced alterations. This study has thus allowed a primary overview and analysis of lightning trauma to human skeletal tissues.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science FACULTY OF HEALTH SCIENCES UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG 2016